Photodegradation Of Diazinon Pesticide In Suspension Of TiO2 - La Ode Ahmad Nur Ramadhan; Amiruddin Amiruddin (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2013)
Study on photodegradation of diazinon pesticide in suspension of TiO2 under ultra violet (UV) illumination was conducted. The aims of study are to determine the effective mass of titanium dioxide (TiO2), the effect of catalyst in initial concentration, the half time, the rate constant, and the rate of degradation reaction. Experimental photocatalytic reactor model was designed and constructed as suspension reactor. Determination of the effective mass of TiO2, the concentration of diazinon residu was performed by HPLC . The concentrations of illuminated diazinon solution were colected as various effective mass of TiO2 and expressed as the concentration vs the mass of TiO2. The mass of TiO2 in minimum diazinon concentration was a the effective mass. The concentration of illuminated diazinon and illumination time relationships was expressed in the graph as ln C/C0 = - k t and regarded as a pseudo first-order. The half time, the rate constant, and the degradation rate was analyzed from the graph. The results show that the photocatalytic degradation of pesticide diazinon by using TiO2 under UV illumination was run effectively in the mass of 12.5 mg for the diazinon concentration of 25 mg/l. The decreasing of initial concentration of diazinon is 90.4 % in 120 minutes. The half time, the rate constant, and the degradation rate are 36,869 minute, 0.0188 /minute, and 0,470 mg/l minute, respectively. Keywords : Kinetic, degradation, diazinon, TiO2